Does conflict-driven internal displacement influence demand for agricultural inputs? Evidence from Nigeria - Amare, Mulubrhan; Ambler, Kate; Bamiwuye, Temilolu; Bloem, Jeffrey R.; Misra, Rewa S.; Wagner, Julia (International Food Policy Research Institute, 2024)
Smallholder farmers in northeastern Nigeria face interrelated challenges of food insecurity, climate change impacts, and conflict. The region has some of the country’s highest levels of food insecurity, and increasingly volatile rainy seasons have led to massive floods, depleted soil quality, and disrupted agricultural growing seasons.